Factors contributing to women trafficking in Malaysia :perspectives from policy maker, implementersand non-governmental organization / Nur Zulaikha Afifah Abd Rohim and Yarina Ahmad - Abd Rohim, Nur Zulaikha Afifah; Ahmad, Yarina (Universiti Teknologi MARA, Shah Alam, 2017)
In today's globalized world, almost every country across the world is affected by human trafficking activities where Malaysia is also not excluded. The case involving women trafficking is among the main concern in Malaysia as it poses a great challenge to detect the crime due to its clandestine and complexity in nature. In addition, trafficking in women is a tragic deprivation of human rights mostly in the forms of sexual exploitation and forced labor. It threatens the security and also indirectly affecting the socio-economic condition of the country. The purpose of this paper is to explore on the contributing factors towards women trafficking issue in Malaysia. The study adopts a qualitative research method by using semi-structured in-depth interviews with six key persons from the Ministry of Home Affairs, Royal Malaysia Police and National Human Rights Commission (SUHAKAM). The findings revealed that trafficking in women is an increasing issue in Malaysia. The main factor that influence high number of women being trafficked is migration due to weak border security protection and smuggling. Following that, law enforcement is also another main factor due to various obstacles and challenges that hinders the effectiveness of the implementation process. Other important factors include globalization, profitable business and corruption. This study recommends that more awareness, capacity building, coordination and enhancement in term of policy formulation and enforcement are needed to combat this crime to its roots.